2020
DOI: 10.1177/0162353220955225
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency and Giftedness: The Role of Language Comprehension in Gifted Identification and Achievement

Abstract: English learners (ELs) are the fastest growing population of students in the United States and currently represent nearly 10% of public school enrollment; however, they also constitute less than 3% of gifted program enrollment in these schools. Although an increasing number of studies explore this underrepresentation, research that specifically examines the role of language proficiency in gifted identification is limited. This study explored the role of several factors on ELs’ time to reclassification (the poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Additionally, neither state nor any districts explicitly included the use of local norms in their identification processes. This finding, coupled with the infrequent use of universal screening processes at the district level as recommended by the outcomes of recent studies (Hamilton et al, 2020; Matthews and Rhodes, 2020; McBee et al, 2014; Mun et al, 2020; Olszewski-Kubilius and Clarenbach, 2012; Peters, 2022; Plucker and Peters, 2018), raises the question about what types of qualified students are being left behind with the use of outdated methods of identification. The use of local norms is a more mathematically complex practice and requires that school districts rely on internal calculations at the district and/or school level for appropriate implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, neither state nor any districts explicitly included the use of local norms in their identification processes. This finding, coupled with the infrequent use of universal screening processes at the district level as recommended by the outcomes of recent studies (Hamilton et al, 2020; Matthews and Rhodes, 2020; McBee et al, 2014; Mun et al, 2020; Olszewski-Kubilius and Clarenbach, 2012; Peters, 2022; Plucker and Peters, 2018), raises the question about what types of qualified students are being left behind with the use of outdated methods of identification. The use of local norms is a more mathematically complex practice and requires that school districts rely on internal calculations at the district and/or school level for appropriate implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to do so could mean missing students who are qualified for gifted education. For instance, research (Hemmler et al, 2022; Hamilton et al, 2020; Long et al, 2022; Peters, 2022; Peters et al, 2019; Peters and Engerrand, 2016) has clearly documented that students of color (Tatum, 2003) are underrepresented in gifted education, so it is plausible to posit that continued misalignment of recommended practices, which have been shown to identify greater numbers of students of color (e.g., Card & Giuliano, 2016) and policy implementation can risk perpetuating the view that gifted education is elitist and inequitable.…”
Section: Discussionmentioning
confidence: 99%
“…Raw disparities. Hamilton et al (2020) reported notable raw disproportionality rates by language status based on U.S. Dept. of Education Data.…”
Section: English Learnersmentioning
confidence: 99%
“…In other words, these marginalized students fail to meet the traditional criteria for identification. Research showed that underrepresentation might be a result of misconceptions, teacher bias, as well as the use of screening techniques (e.g., nonverbal tests to identify non-native English speakers) that are inappropriate ( Hamilton et al, 2020 ). Researchers in gifted education advise employing a variety of techniques to identify individuals for gifted programs, such as alternative assessment measures, and multiple criteria adoption ( Ecker-Lyster and Niileksela, 2017 ; Dixson et al, 2020 ; Lee et al, 2022 ).…”
Section: Refugee and Underrepresented Gifted Students In Lebanonmentioning
confidence: 99%